2004
DOI: 10.1039/b106617j
|View full text |Cite
|
Sign up to set email alerts
|

Design of chiral dimesogens containing cholesteryl groups; formation of new molecular organizations and their application to molecular photonics

Abstract: Photoresponsive liquid crystals and organogels are finding increasing application in information technology and photonics. In this tutorial review, the authors describe how weak intermolecular interactions facilitate molecular organization of cholesterol-containing dimesogens to form such materials. Design considerations and photoresponsive properties of both organogels and glassy liquid crystals are discussed and their applications to molecular photonics highlighted. The review will be of value to readers int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(70 citation statements)
references
References 34 publications
0
70
0
Order By: Relevance
“…Using ChLCs, reversible colored states can be achieved for applications in full-color displays without the need for any color filter or polarizer. [1,2] The pitch of ChLCs is generally sensitive to the external perturbation and, thus, the LC state must be vitrified for memory-effect-related applications. We have demonstrated that light-driven erasable color recording is possible by doping the glass-forming ChLC, CD8 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ChLCs, reversible colored states can be achieved for applications in full-color displays without the need for any color filter or polarizer. [1,2] The pitch of ChLCs is generally sensitive to the external perturbation and, thus, the LC state must be vitrified for memory-effect-related applications. We have demonstrated that light-driven erasable color recording is possible by doping the glass-forming ChLC, CD8 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The sensitivity of ChLCs to external parameters, such as temperature, the presence of impurities, and light, has led to many practical applications and has been the subject of much theoretical research. [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several mechanisms have been proposed to explain the role that the dopant molecules play in the modulation of the macroscopic chirality of ChLCs. [11,[24][25][26][27][28] Recently, we reported that the mechanism of the helical-pitch shift that is induced by achiral dopants (as well as in dimesogenic compounds) is due to enhancement of smectic A (SmA)-like clusters in the cholesteric phases.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The use of circularly polarized light (CPL) as the irradiation source has led to enantiomeric excess values in two chiral domains in the Bx phase of bent-core molecules. [9] Moreover, supramolecular chirality photoinduced by CPL has been reported in azopolymers [10] and in main-chain polymeric liquid-crystal systems doped with azobenzene-containing W-shaped molecules.…”
mentioning
confidence: 99%
“…In a recent series of papers, a new molecular design concept, wherein nematic and chiral groups are chemically bonded to a volume-excluding core to prevent crystallization upon cooling, has been detailed. [6][7][8][9][10][11][12] These materials, however, were prepared using a multiple synthetic step and/or troublesome workup procedures. For the applications described above, materials with the highest possible glass transition temperature are needed to ensure sufficient room temperature stability of the devices.…”
Section: Introductionmentioning
confidence: 99%